Facile synthesis of fluorescent hetero[8]circulene analogues with tunable solubilities and optical properties. Issue 48 (7th November 2019) - Matsuo, Yusuke; Chen, Fengkun; Kise, Koki; Tanaka, Takayuki; Osuka, Atsuhiro
Abstract : Highly twisted quasi-aza[8]circulene and planar triazaoxa[8]circulene have been prepared, which exhibited intriguing optical properties. Abstract : Hetero[8]circulenes are an interesting class of polycyclic heteroaromatic molecules having rigid and planar structures, which are promising in light of their potential applications for OLEDs, OFETs and so forth. Although their synthetic methods have been developed in some specific cases, a facile synthetic protocol of novel hetero[8]circulenes with tunable properties is highly desirable. We herein report the unexpected formation of methoxy-substituted quasi-aza[8]circulene and its conversion into unprecedented triazaoxa[8]circulene. The structures and optical properties were comparatively studied. Remarkably, triazaoxa[8]circulene is highly soluble in THF, acetone and DMSO mainly because of effective hydrogen-bonding of the NH moieties to these solvents. Their highly soluble nature in various solvents enabled us to study the solvent effects of these molecules. In particular, triazaoxa[8]circulene displays a high fluorescence quantum yield of 0.72 in DMSO. Furthermore, enantiomeric separation of highly distorted quasi-aza[8]circulene was successfully achieved by chiral HPLC. Thus, these novel hetero[8]circulene derivatives are practically useful fluorescent nanographene-like molecules with intriguing optical properties.